1994
DOI: 10.1007/bf01971313
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and characteristics of urinary tract infections caused byCorynebacterium urealyticum (Corynebacterium group D2)

Abstract: The incidence and characteristics of urinary tract infections caused by Corynebacterium urealyticum were studied prospectively in 20,766 urine samples. Corynebacterium urealyticum was isolated from 67 samples (0.32%). Twenty-four percent of the patients from whom Corynebacterium urealyticum was isolated showed mild symptoms and had no risk factors other than prolonged hospitalization and previous antibiotic treatment. Sixty percent of the patients had urinary tract-related symptoms. The main risk factors were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
5

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 12 publications
0
29
0
5
Order By: Relevance
“…About 15 million (>25%) of 57 million annual deaths worldwide are estimated to be related directly to infectious diseases (WHO, 2004). One most interesting aspect of the work of great applied significance is the ability of the medicinal smoke to completely eliminate human pathogenic bacteria Corynebacterium urealyticum causing urinary tract infection (Nebreda-Mayoral et al, 1994), Kocuria rosea causing catheterrelated bacteremia (Altuntas et al, 2004), Staphylococcus lentus causing splenic abscess (Karachalios et al, 2006), Staphylococcus xylosus causing acute polynephritis (Angelina et al, 1982), Tsukamurella inchonensis causing acute myelogenous leukemia (Yassin et al, 1995), Enterobacter aerogenes (Klebsiella mobilis) nosocomial infections (Peres-Bota et al, 2003), Sphingobacterium spiritovorum causing extrinsic allergic alveolitis (Sato and Jiang, 1996) and Sphingomonas sanguinis causing nosocomial non-life-threatening infections (Li et al, 2004) (Table 1). Smoking has some important benefits compared to other drug routes of administration.…”
Section: Resultsmentioning
confidence: 99%
“…About 15 million (>25%) of 57 million annual deaths worldwide are estimated to be related directly to infectious diseases (WHO, 2004). One most interesting aspect of the work of great applied significance is the ability of the medicinal smoke to completely eliminate human pathogenic bacteria Corynebacterium urealyticum causing urinary tract infection (Nebreda-Mayoral et al, 1994), Kocuria rosea causing catheterrelated bacteremia (Altuntas et al, 2004), Staphylococcus lentus causing splenic abscess (Karachalios et al, 2006), Staphylococcus xylosus causing acute polynephritis (Angelina et al, 1982), Tsukamurella inchonensis causing acute myelogenous leukemia (Yassin et al, 1995), Enterobacter aerogenes (Klebsiella mobilis) nosocomial infections (Peres-Bota et al, 2003), Sphingobacterium spiritovorum causing extrinsic allergic alveolitis (Sato and Jiang, 1996) and Sphingomonas sanguinis causing nosocomial non-life-threatening infections (Li et al, 2004) (Table 1). Smoking has some important benefits compared to other drug routes of administration.…”
Section: Resultsmentioning
confidence: 99%
“…, Nebreda‐Mayoral et al . ). In a previous study, most CU isolates were found to be susceptible to enrofloxacin (Bailiff et al .…”
Section: Discussionmentioning
confidence: 97%
“…In our country, the use of vancomycin and teicoplanin is prohibited for treating veterinary patients, and this might explain the absence of clinical recovery in some of these cases. Tetracyclines and fluoroquinolones have also been used with great success in many patients with CU-UTI (Soriano et al 1990, Nebreda-Mayoral et al 1994. In a previous study, most CU isolates were found to be susceptible to enrofloxacin (Bailiff et al 2005) in dogs and cats.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of UTI in the presence of urine with alkaline pH and struvite crystals are strongly suggestive of infection with C. urealyticum (12). The incidence of UTIs due to C. urealyticum is less than 2% worldwide (13). Treatment of C. urealyticum urinary infection may be difficult.…”
Section: Resultsmentioning
confidence: 99%